2016
DOI: 10.1007/s11661-015-3313-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Pulse Electrodeposited Lead-Free Tin-Based Sn/ZrSiO4 Nanocomposite Coatings

Abstract: The Sn-based ZrSiO 4 nanocomposite coatings have been synthesized by pulse co-electrodeposition technique from an aqueous electrolyte containing SnCl 2 AE2H 2 O, C 6 H 17 N 3 O 7 , Triton X, and varying amounts of nano-sized ZrSiO 4 particles (0,5,10,15,20,25,30, and 35 g/L). As-deposited films have been analyzed using X-ray diffraction, scanning electron microscope equipped with an energy dispersive X-ray spectrometer, and transmission electron microscope. The microhardness, wear as well as corrosion property… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…The authors found a great improvement in corrosion resistance of coatings in the presence of graphene oxide which improved the homogeneity of the HEA coating matrix and prevented localized corrosion [72]. However, despite all this progress, the electroplated HEAs are still in the emerging stage, due to the complexity of processing parameters and multicomponent alloy deposition, which is a tedious task given the interrelated pulse deposition parameters [95,98,100]. Dmitry Moskovskikh et al produced (Hf 0.2 Nb 0.2 Ta 0.2 Ti 0.2 Zr 0.2 )N, which demonstrated outstanding hardness and fracture toughness (33 GPa, 5.2 MPa•m 1/2 ), compared to other reported binary and high entropy ceramics coatings [101].…”
Section: Methods Of Fabrication Of Hea Coatingsmentioning
confidence: 99%
“…The authors found a great improvement in corrosion resistance of coatings in the presence of graphene oxide which improved the homogeneity of the HEA coating matrix and prevented localized corrosion [72]. However, despite all this progress, the electroplated HEAs are still in the emerging stage, due to the complexity of processing parameters and multicomponent alloy deposition, which is a tedious task given the interrelated pulse deposition parameters [95,98,100]. Dmitry Moskovskikh et al produced (Hf 0.2 Nb 0.2 Ta 0.2 Ti 0.2 Zr 0.2 )N, which demonstrated outstanding hardness and fracture toughness (33 GPa, 5.2 MPa•m 1/2 ), compared to other reported binary and high entropy ceramics coatings [101].…”
Section: Methods Of Fabrication Of Hea Coatingsmentioning
confidence: 99%
“…One of the causes of peel is residual stress accumulated during plating in the Cu films. The Stoney formula was used to calculate the residual stress R S of the film: where E s is Young’s modulus, t s and t f are the thickness of the substrate and film, r 0 and r are the radii of curvature of the substrate before and after film deposition, and v s and v f are the Poisson’s ratio of the substrate and film. The values of PET are as follow: E s = 2 GPa, t s = 1 mm, and v s = 0.43.…”
Section: Experimental Proceduresmentioning
confidence: 99%
“…The formation of grooves was due to the plowing action of the indenter ball, leading to the hardening of the coating layer and further tearing by the harder WC indenter [37,38]. Additionally, at higher loads, the concentration of oxygen was prominent, which showed oxidative wear operating in a higher load regime due to the continuous increase in the rubbing of the surface by the ball indenter at higher loads [39]. A rough surface of the ball indenter showed material transfer from coatings to ball surface.…”
Section: Wear Tracksmentioning
confidence: 99%